Globalizing nursing science: analysis of nursing’s participation in the open access movement from 1993 to 2014 - Nick, Jan M (International Journal of Advanced Nursing Studies, 2015)
Background: The traditional journal subscription model restricts access to scholarly information since proprietary fee-based databases charge high subscription fees, do not provide access to all journals in the same geographic region, and include minimal access to research journals from other countries. This practice insulates nursing knowledge, causes duplication rather than replication of research, and results in a lack of breadth and depth to our science.Objective: Describe the state of nursing participation in the Open Access (OA) movement.Methods: Using a descriptive, exploratory approach, all nursing journals in the Directory of Open Access Journals (DOAJ) data warehouse were extracted, tagged, and analyzed.Results: Sixty-two nursing journals from 23 countries have registered as Open Access. Brazil publishes the largest number of OA nursing journals (14), followed by the U.S. (9) and Spain (9). Two countries publish four OA nursing journals (Canada, Iran), while the remaining 18 countries publish one or two OA nursing journals. Fifty percent publish in either Spanish, Portuguese, or Spanish/Portuguese, while another one-third (32%) publish in English. Importantly, 82% of OA Nursing journals do not require article processing charges; of those who do have APCs, the majority (66%) are 300 or less.Conclusions: Although nursing participated early in the OA movement, growth has been consistent but sluggish. Neither the size of the country nor economic status seem to have a strong influence on decisions to produce OA nursing journals. Encouraging participation in OA will advance the science of nursing by allowing broader and more coordinated access to information to the global community.